MAKNA KANYOUKU YANG BERKAITAN DENGAN BAGIAN TUBUH HANA (HIDUNG), KUCHI (MULUT), MIMI (TELINGA), ME (MATA), DAN SHITA (LIDAH) - Anggun Widiyani (Sekolah Tinggi Bahasa Asing (STBA) Yapari-ABA Bandung, 2016)
Kanyouku is a group of words (phrase) that has specific meaning (the meaning cannot betranslated word for word thereof). The term kanyouku cannot be translated directly into Bahasa Indonesia, but can still be predicted through the relation between idiomatic and lexical meaning of the words that form the phrase. This study was a qualitative study aiming at describing the relationship between lexical and idiomatic meaning in kanyouku using the following words: hana (nose), kuchi (mouth), mimi (ears), me (eyes), and shita (tongue). The findings of the research suggest that: kanyouku ‘hana ga takai’ has partial(tongue). The findings of the research (bbuubbuunn) and whole(tongue). The findings of the research suggest that: ( zzeenntataii) relationship as well as cause-effect relationship; kanyouku kuchi ga omoihas metonymic meaning extension due to cause-effect process; and kanyouku me o toosu, mimi ga itai, andshita o makuhave spatial and time relationship. Lexical and idiomatic meaning relationship in kanyouku was dominated by metonymic relations (relationship. Lexical and idiomatic meaning relationship metonymic relations (kanyu kanyu) in the forms of cause-effect, spatial and time, and part for whole relations.